Quantitative sequential modelling approach to estimate the reliability of computer controlled pneumatically operated pick-and-place robot - Pandian Durairaj, Satheesh (Strojniški vestnik, 2025)
Pneumatically controlled pick-and-place robots are an integral part of contemporary manufacturing processes and have the potential to enhance the precision and velocity of numerous production-related tasks. As automation continues to disrupt various sectors, the role of these robots is becoming increasingly crucial. Achieving peak performance in robot operations requires a relentless focus on safety and reliability. As a result, subsequence reliability should be considered carefully from the initial part of the design phase. Roboticists need to identify the dependable subsequences and parts of the robot’s operational framework in prior to access the system’s overall reliability. This analytical technique aids in component identification and demonstrates how to measure redundancy to ensure dependability and robustness. Based on recent theories and frameworks, the researchers can understand the factors that have more impact towards the reliability of pneumatically driven pick-and-place robots. Thus, this research work improves an exhaustive dependability analysis of a computer-controlled pneumatically operated pick-and-place robot. As part of our methodology, we use modern LabVIEW software to conduct a comprehensive failure analysis and estimate the reliability of the sequence.
Keywords: analiza napak; automation; avtomatizacija; failure analysis; LabVIEW programska oprema; LabVIEW software; pneumatically controlled pick-and-place robots; pnevmatski prijemalno-polagalni (pick-and-place) roboti; reliability; zanesljivost